Utilities Associated with the Treatment of Growth Hormone Deficiency (GHD): A Time Trade-off (TTO) Study in the UK and Canada - Kirsch S; Butler G; Jensen LDF; Okkels A; Yssing C; Håkan-Bloch J (Patient Related Outcome Measures)
Susan Kirsch,1 Gary Butler,2 Lasse de Fries Jensen,3 Anna Okkels,4 Cecilie Yssing,4 Jonas Håkan-Bloch3 1Department of Pediatric Endocrinology, Hospital for Sick Children, Toronto and Oak Valley Health Hospital, Markham, Ontario, Canada; 2Department of Paediatric Endocrinology, University College London Hospitals, and UCL Great Ormond Street Institute of Child Health, London, UK; 3Novo Nordisk, Søborg, 2860, Denmark; 4EY Godkendt Revisionspartnerselskab, Frederiksberg, 2000, DenmarkCorrespondence: Lasse de Fries Jensen, Novo Nordisk, Vandtårnsvej 108-110, Søborg, 2860, Denmark, Tel +45 34482020, Email LDFJ@novonordisk.comPurpose: Growth hormone deficiency (GHD) causes decreased growth rate in children, resulting in short stature in childhood and adulthood. Daily subcutaneous injections with growth hormone (GH) have been standard treatment. Newer weekly GH formulations now exist. This study estimates utilities associated with GHD treatment for both people with the disease and caregivers by employing time trade-off (TTO) methodology.Methods: Three online surveys were conducted amongst the general population in the UK and Canada. Based on a pilot, data collection was conducted in two surveys only (Survey A and Survey B). In Survey A, adults aged ≥ 18 years evaluated health states as if they were receiving injections themselves. In Survey B, adults with a child < 15 years evaluated health states as if they were administering injections to a child. The surveys assessed device complexity, injection frequency, injection pain, needle visibility and storage possibilities.Results: 2026 and 2028 respondents completed Survey A and Survey B, respectively. Of these, 1782 respondents and 1678 respondents were valid for inclusion. Avoiding weekly injection pain was associated with a significant utility gain of 0.030 (95% CI 0.026– 0.035, p< 0.001) in Survey A and 0.044 (95% CI 0.038– 0.051, p< 0.001) in Survey B. Additionally, less complex injection devices and lower injection frequencies had a significant impact in both Survey A (0.020, 95% CI 0.016– 0.025, p< 0.001; 0.009, 95% CI 0.005– 0.014, p< 0.001) and Survey B (0.008, 95% CI 0.002– 0.014, p=0.006; 0.009, 95% CI 0.003– 0.014, p=0.003).Conclusion: Several aspects are associated with a significant impact on utilities for people with GHD and potential caregivers. Treatment options without injection pain, a time-consuming and complex injection process and daily injections are expected to result in higher health-related quality of life. These results may inform future economic evaluations and treatment choices.Keywords: caregiver, children, health-related quality of life, survey